Imaging the Proangiogenic Effects of Cardiovascular Drugs in a Diabetic Model of Limb Ischemia. (3rd February 2019) - Goggi, J. L.; Haslop, A.; Boominathan, R.; Chan, K.; Soh, V.; Cheng, P.; Robins, E. G.; Bhakoo, K. K.
Abstract : Purpose . Peripheral artery disease (PAD) causes narrowing of arteries in the limbs, leading to tissue ischemia, gangrene, and eventually limb amputation. The presence of diabetes greatly exacerbates the course of PAD, accounting for the majority of lower limb amputations. Therapeutic strategies focussing on macrovascular repair are less effective in diabetic patients where smaller vessels are affected, and proangiogenic therapies offer a viable adjunct to improve vascularisation in these at risk individuals. The purpose of the current study was to assess the proangiogenic effects of drugs routinely used to treat cardiovascular disease in a diabetic murine model of hind limb ischemia longitudinally using multimodal imaging. Procedures . Diabetic mice underwent surgical intervention to induce hind limb ischemia and were treated with simvastatin, metformin, or a combination orally for 28 days and compared to diabetic and nondiabetic mice. Neovascularisation was assessed using [ 18 F]FtRGD PET imaging, and macrovascular volume was assessed by quantitative time of flight MRI. At each imaging time point, VEGF expression and capillary vessel density were quantified using immunohistochemical analysis, and functional recovery and disease progression were assessed. Results . Combined use of simvastatin and metformin significantly increased neovascularisation above levels measured with either treatment alone. Early angiogenic events were accurately assessed using PET [ 18 F]FtRGD, showing maximal retention in the ischemic hind limb by day 8, which translated to a sustained increase in vascular volume at later time points. Immunohistochemical analysis shows that combined therapy significantly increased VEGF expression and capillary density (CD31 + ) in a similar time course and also slowed disease progression while simultaneously improving functional foot use. Conclusions . Combined treatment with simvastatin and metformin led to a significant improvement in limb angiogenesis, vascular volume, and sustained functional recovery in a diabetic murine model of HLI. PET imaging with [ 18 F]FtRGD provides a robust method for early detection of these proangiogenic effects preclinically and may be useful for the assessment of proangiogenic therapies used clinically to treat diabetic PAD patients.